Porównanie składu ciała i poziomu wybranych koordynacyjnych zdolności motorycznych u dzieci w wieku 8-13 lat w zależności od ich masy urodzeniowej = Comparison of composition of body weight and the level of selected coordination motor abilities in children aged 8-13 years depending on their birth weight - Rzeszotek, Klaudia; Rzeszotek, Mariusz; Rynkiewicz, Tadeusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Health risks that may occur at a later age in children with fetal dystrophy are well-known. There is a lack of research on motor development and changes in body composition in children with fetal dystrophy. The results so far are contradictory. Hence, the study was undertaken to indicate the differences in body composition, ability to respond quickly and ability to maintain dynamic balance in children aged 8-13 years, depending on hypotrophy and hypertrophy at birth.
Keywords: birth weight; gestational age; body composition; reaction time; body balance; masa urodzeniowa; budowa ciała; czas reakcji; równowaga ciała